Uzbekistan : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
This paper discusses 2012 Article IV Consultation of Republic of Uzbekistan. Uzbekistan has been experiencing strong momentum in economic growth supported by sustained public investment and increased prices for commodity exports. The IMF report suggests that it is important to ease the restrictiveness of the foreign exchange and trade regimes, as it impedes the development of the financial and private sectors and distorts resource allocation. Improvement economic data quality and transparency should also be a high- priority item in the action list.